2017
DOI: 10.2147/opth.s143246
|View full text |Cite
|
Sign up to set email alerts
|

Novel grid combined with peripheral distortion correction for ultra-widefield image grading of age-related macular degeneration

Abstract: PurposeEyes with age-related macular degeneration (AMD) often harbor pathological changes in the retinal periphery and perimacular region. These extramacular changes have not been well classified, but may be phenotypically and functionally relevant. The purpose of this study was to demonstrate a novel grid to systematically study peripheral retinal abnormalities in AMD using geometric distortion-corrected ultra-widefield (UWF) imaging.MethodsThis is a cross-sectional observational case series. Consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…8 Since more standard images were obtained in published studies that utilized the software developed by Optos to eliminate torsion in images obtained in the upward and downward gaze fixation positions of the device, these studies seem to have less subjectivity. 4,9 In the present study, we evaluated images taken without using such software separately. In future studies, it may be beneficial to use software that ensures standardization in order to prevent analytical errors that may result from subjective evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Since more standard images were obtained in published studies that utilized the software developed by Optos to eliminate torsion in images obtained in the upward and downward gaze fixation positions of the device, these studies seem to have less subjectivity. 4,9 In the present study, we evaluated images taken without using such software separately. In future studies, it may be beneficial to use software that ensures standardization in order to prevent analytical errors that may result from subjective evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted to date present different views regarding how the midperipheral area (i.e., the retinal region referred to as zone 2) should be calculated. 4,5,7,8,9,10,11,12 When planning the present study, we accepted an area of 3 DD as zone 1 and an area of 9 DD as zone 2 (considered the midperiphery). 5,6 Confusion regarding the definition of the midperipheral region in the literature is preventing its standardization in current studies and necessitates the establishment of standard measurements which can be incorporated into emerging technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Each channel was viewed separately and analysed with the Optomap Vantage V2 Software with ProView™ option, which minimises distortion and magnification irregularities. 16 The following data were evaluated (pre-treatment and at the last follow-up visit): Snellen visual acuity (hand perception was noted as 20/2000), tumour location as well as post PBRT retinopathy (telangiectasias, microaneurysms, neovascularisation, vitreous haemorrhage, hard exudates, cotton wool spots, retinal edema) ( Figure 1); maculopathy (macular edema); optic neuropathy (pale optic disc, disc edema along with haemorrhage and microangiopathy); and toxic tumour syndrome (all of the above plus exudative retinal detachment and/or rubeosis iridis and neovascular glaucoma). 4 A number of parameters on the Optos images were documented (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…; Oellers et al. ). However, the effects of distortion have not yet been assessed in ocular oncology clinical practice.…”
Section: Introductionmentioning
confidence: 96%
“…A narrow-field view, as obtained with standard fundus photography (SF), needs a reconstructed montage using multiple narrow-field fundus photography to visualize the outer borders of large tumours and those located at the periphery (Kim et al 2009). This limitation can be overcome with UWF, but as the 3D spherical eye is converted to a 2D image distortion could potentially be a problem for UWF devices that cover a larger part of the fundus (Doelemeyer & Petrig 2000;Lee et al 2007;Nicholson et al 2018), and it has previously been shown that while distortion is minimal near the posterior pole of the eye and increases as the peripheral retina is approached (Daftari et al 2010;Oellers et al 2017). However, the effects of distortion have not yet been assessed in ocular oncology clinical practice.…”
Section: Introductionmentioning
confidence: 99%